Skemman og opinn aðgangur. Skýrsla um skil nemenda við Háskóla Íslands í Skemmuna veturinn 2009-2010 og hlutfall ritgerða í opnum aðgangi - Áslaug Agnarsdóttir 1949- (2011)
Styttri gerð þessarar skýrslu birtist sem grein í tímaritinu Bókasafnið 2011 Skemman is an institutional repository used by six Icelandic universities to archive and preserve electronic copies of academic research as well as students‘ theses. In late November 2010 a total of nearly 7000 authors had submitted their work to Skemman. This article examines the percentage of theses submitted by students at The University of Iceland during the academic year 2009-2010 as well as the percentage of open access theses. Students are required to submit an electronic copy of their final thesis but can choose between open or closed access. The University of Iceland Council voted to make the submission of electronic copies of final theses mandatory in February 2008. Later that year The National and University Library took over the running of the repository and started to archive electronic copies of theses from the University of Iceland in October 2008. The first academic year of 2008-2009 was not very successful since the repository lacked both formal rules and the necessary publicity. Students graduate from The University of Iceland three times a year, in October, February and June. Results for the academic year 2009-2010 were as follows: In October 81% of those graduating submitted their theses to Skemman. Of these 67% were open access. In February 86% of the graduates submitted their theses and 71% of these were open access. In June 93% of all graduates submitted their theses and again 71% were open access. Whereas the percentage of submissions went up 12%, the percentage of open access theses only increased 4%. There is not an obvious difference between the five schools of The University of Iceland as regards open access but if faculties within the schools are examined a huge difference appears. In June 2010 only 24% of those graduating from the Faculty of Law chose open access as opposed to 97% of those graduating from the Faculty of Nursing. The University of Iceland has not implemented a policy of open access but ...